Perilaku Petugas dalam Pengelolaan Sampah di Lokawisata - Marsum Marsum; Lagiono Lagiono; Budi Triyantoro (Jurnal Riset Kesehatan, 2015)
This descriptive observational research aims to describe the facilities and personnel to conduct waste management in Baturraden Tourism in Banyumas District. The results are: 52.3% of the waste management is in the category of poor, the waste management facilities is quite good (68.3%), the leader’s support is good (83.3%), and the behavior of the dustmen in the waste management is also good (83.3%). In conclusion, the waste management in Baturraden Tourism in Banyumas District has not been implemented optimally yet. There are still some facilities that are broken. The behavior of the support workers and leaders is good, but it is only intended to secure/ collect the rubbish from the rubbish dump. We suggest the leadership in Baturraden to proposed finance plan for the improvement in the supply of facilities such as temporary trash container and to increase the frequency of the transport schedule of the waste. It is also suggested to grant some awards to the selected officers for their good behavior in waste management in order to survive well. The management also need to facilitate more trainings for the workers in waste management. a